Application of Ti 3 C 2 MXene Quantum Dots for Immunomodulation and Regenerative Medicine - Rafieerad, Ali Reza; Yan, Weiang; Sequiera, Glen Lester; Sareen, Niketa; Abu‐El‐Rub, Ejlal; Moudgil, Meenal; Dhingra, Sanjiv (Wiley, 2019)
Inflammation is tightly linked to tissue injury. In regenerative medicine, immune activation plays a key role in rejection of transplanted stem cells and reduces the efficacy of stem cell therapies. Next-generation smart biomaterials are reported to possess multiple biologic properties for tissue repair. Here, the first use of 0D titanium carbide (Ti3C2) MXene quantum dots (MQDs) for immunomodulation is presented with the goal of enhancing material-based tissue repair after injury. MQDs possess intrinsic immunomodulatory properties and selectively reduce activation of human CD4+IFN-γ+ T-lymphocytes (control 87.1 ± 2.0%, MQDs 68.3 ± 5.4%) while promoting expansion of immunosuppressive CD4+CD25+FoxP3+ regulatory T-cells (control 5.5 ± 0.7%, MQDs 8.5 ± 0.8%) in a stimulated lymphocyte population. Furthermore, MQDs are biocompatible with bone marrow-derived mesenchymal stem cells and induced pluripotent stem cell-derived fibroblasts. Finally, Ti3C2 MQDs are incorporated into a chitosan-based hydrogel to create a 3D platform with enhanced physicochemical properties for stem cell delivery and tissue repair. This composite hydrogel demonstrates increased conductivity while maintaining injectability and thermosensitivity. These findings suggest that this new class of biomaterials may help bridge the translational gap in material and stem cell-based therapies for tissue repair and treatment of inflammatory and degenerative diseases. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim